Pengaruh Beban Kerja, Stress Kerja, Dan Lingkungan Kerja Fisik Terhadap Turnover Intention Karyawan Teknisi Instalasi Internet - Hasyim, Hasyim; Ramdani, Ramdani (Riviera Publishing, 2025)
The purpose of this study is to investigate the direct influence of workload, work stress, and physical work environment on turnover intention, to determine the direct influence of workload, work stress and physical work environment on turnover intention. As well as the combined influence of workload, work stress and physical work environment on turnover intention in the internet installation technician section of PT Rizki Persada Sejati. Data collection was carried out using questionnaires distributed online using google from through social media such as Whatsapp. The population in this study is all employees of the production department of the telecommunications company PT Rizki Persada Sejati which totals 400 people. The questionnaire was collected from 155 respondents and the data was processed using multiple regression analysis tools. From the results of the research, it was found that workload had no effect on turnover intention. Work stress has a positive effect on turnover intention. The physical work environment has no effect on turnover intention, and workload, work stress and physical work environment have an equal effect on turnover intention.